The effect of focused corrective feedback on the use of articles in essays by ESL learners / Carolyn Ann Angus - Carolyn Ann , Angus (2017)
This study investigated the effect of focused direct written corrective feedback (WCF) on the use of two functions of articles in the written narratives of 43 lower-intermediate Malaysian ESL learners. Using a simplified adaptation of Sheen’s 2007 study, this study used three intact ESL classes to form three groups: direct-only WCF (DCF, n=16), direct metalinguistic WCF (DME. n=12), and the control group (n=15). The study had a pretest-treatment-posttest-delayed posttest configuration with four CF treatment sessions and a short questionnaire survey with both experimental groups. This study found that receiving focused direct WCF does help improve students’ written accuracy in the use of two functions of English articles. However, no difference was found between receiving direct-only WCF (DCF) and direct WCF with metalinguistic comments (DME). In terms of students’ perceptions of its usefulness, both experimental groups indicated that receiving focused direct WCF made it easier for them to notice their errors and that it made them think about the errors they made. However, the participants who received direct WCF with metalinguistic comments (DME) significantly preferred receiving their form of WCF and that they also thought it was much easier to notice their errors when corrected that way.